Translating Ideophones from Arabic into English: A Comparative Analytical Study Between Two Translations of Al-Asmai’s Poem the Sound of the Nightingale’s Whistle: ترجمة الأيديوفونات من العربية إلى الإنػليزية: دراسة مقارنة تحليلية بين ترجمتين لقصيدة صوت صفير البلبل للأصمعي - Haniche , Hossam Eddine (Maalim, 2026)
The importance of this research, entitled "Translating Ideophones from Arabic into English: A Comparative Analytical Study Between Two Translations of Al-Asmai’s Poem the Sound of the Nightingale's Whistle", lies in studying of the methods and techniques used in translating ideophones from Arabic into English. The research aims at comparing and analyzing two English translations of the poem "The Sound of the Nightingale's Whistle" by the poet Al-Asmai, based on the Arabic version. The results indicated that translators use equivalence, translation by omission, borrowing, and transposition to render ideophones from Arabic into English.